2019
DOI: 10.21470/1678-9741-2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency is not Associated with Higher Levels of SYNTAX Score

Abstract: Objective To evaluate the association between serum vitamin D (vitD) level and SYNTAX (synergy between percutaneous coronary intervention with taxus and cardiac surgery) score (SS). Methods The medical records of consecutive patients, who underwent coronary artery bypass graft surgery, were retrospectively reviewed. The study group consisted of 158 patients. Biochemical, clinical, and echocardiographic parameters and SS were evaluated in all patients. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Eight studies ( 1 , 21 24 , 26 28 ) in our meta-analysis reported postoperative severe events and VitD level. Severe events included postoperative atrial fibrillation (Po-AF) and high SYNTAX score.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Eight studies ( 1 , 21 24 , 26 28 ) in our meta-analysis reported postoperative severe events and VitD level. Severe events included postoperative atrial fibrillation (Po-AF) and high SYNTAX score.…”
Section: Resultsmentioning
confidence: 96%
“…However, 15 articles were excluded by reading the complete articles due to: article type ( n = 1); absence of measurement of VitD levels at required time points or the outcomes described in the criteria of inclusion ( n = 13); not using the standard definition of VitD deficiency ( n = 1). Ultimately, 16 reports ( 1 , 2 , 18 31 ) were included in the meta-analysis ( Figure 1 ). No reports from China met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations